Penal responsibilities of the banking institution for computer errors in the electronic transfer of money - Abou Turabi, bushra; BENMESSAOUD, Chahrazed (Journal of Human Sciences, 2025)
Banking institutions have been applying informatics in their field of work for a long time. At the beginning of the nineties, as a result of the expansion in the use of computers, the information industry emerged, due to its great ability to store information and the ease of retrieving it upon request. The banking institutions sector is considered the sector that benefits most from this development, as it Banking operations as a whole have been affected by the application of information technology in all its operations and financial movements in all its forms and forms Also, in 1977, the US Congress formed a committee concerned with studying the possibility of making an electronic transfer of money using information technology, which recently ended its application in bank transfer systems, and from here began to appear to us the dilemma of computer errors when transferring money electronically, and our article aims to shed light and address these issues. The issue and determining the criminal liability for errors resulting from the electronic transfer of money, who bears responsibility for those errors, and on what basis is criminal liability against the perpetrators of this act How can criminal liability be assigned to the banking institution from which the error resulted? To that end, this study was organized and addressed an explanation of what is meant by criminal liability and the legal conditions that must be met so that the banking institution can be held accountable for those errors, in addition to talking about the direct actor theory as a basis for holding the banking institution accountable for computer errors. Automated.